New evidence on the effects of federal regulations on insider trading: The Insider Trading and Securities Fraud Enforcement Act (ITSFEA) - Garfinkel, Jon A. (Journal of Corporate Finance, 1997)
This paper finds new evidence that the threat of legal sanctions significantly affects the trading behavior of insiders. Specifically, I examine the effects of the Insider Trading and Securities Fraud Enforcement Act (ITSFEA) on insider trading around earnings announcements. Given ITSFEA's stated concern with trading on private information prior to its release, I argue that insiders may respond to the Act by altering the timing of their trades. I find that, following ITSFEA, insiders are more likely to postpone liquidity sales until after negative earnings surprises. I also find that insiders increase their relative emphasis on post-event as opposed to pre-event information based trading. Finally, earnings announcements appear to be more informative in the post-ITSFEA period, consistent with less information based trading in front of earnings announcements, after the Act.